2020
DOI: 10.1115/1.4049282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygenated Biomass Fuels on the Performance of Diesel Engine and After-Treatment System

Abstract: Oxygenated biomass fuels have attracted significant attention due to their contributions in reducing environmental pollution and fossil fuel consumption. In view of stricter emission regulations, the use of these alternative fuels cannot fully meet the requirements, and it needs to be combined with an after-treatment system. In this article, polymethoxy dimethyl ether (PODE) and n-pentanol were blended with diesel (D100 (pure diesel)) at 15% and 20% by volume, respectively, referred to as D85P15, D80P20, D85A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In contrast, there is relatively less research on the DPF performance when fueling with diesel/PODE n mixture. Recently, Zhang et al [32] studied the effect of PODE n addition on the performances of a diesel oxidation catalyst (DOC) and catalytic diesel particulate filter (cDPF) after-treatment system. The results showed that the pressure drop of the cDPF can be greatly reduced by fueling with diesel/PODEn mixture, and thus the active regeneration frequency can be effectively decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is relatively less research on the DPF performance when fueling with diesel/PODE n mixture. Recently, Zhang et al [32] studied the effect of PODE n addition on the performances of a diesel oxidation catalyst (DOC) and catalytic diesel particulate filter (cDPF) after-treatment system. The results showed that the pressure drop of the cDPF can be greatly reduced by fueling with diesel/PODEn mixture, and thus the active regeneration frequency can be effectively decreased.…”
Section: Introductionmentioning
confidence: 99%